Method Development and Validation of RP-HPLC Method for Glimepiride, Pioglitazone Hcl and Metformin Hcl in Tablets - N.Ramathilagam; P.Solairaj (International Journal of Pharmacy and Analytical Research, 2014)
A simple, accurate, precise and linear Isocratic RP-HPLC has been developed and subsequently simultaneous for the determination of glimepiride, pioglitazone Hcl and metformin Hcl in pharmaceutical dosage form. Kromosil C18 (150mm X4.6 mm) 5µ with flow rate of 1ml/min by using JASCO PU-1580 and UV/VIS JASCO UV-1570 at 217nm. The separation was carried out using a mobil phase consisting of the mixture of methanol and 25mM phosphate buffer (pH-2.0) in the ratio of 50 :50. The retention time for glimepiride, metformin Hcl and pioglitazine Hcl were found to be 2.24, 3.76 and 10.20 min. the correlation coefficient was found to be 0.999 for GLI, 0.9993 for PIO and 0.9997 for MET. The mean percentage recovery was found to be 98.58 (GLI), 98.30 (PIO) and 98.87 (MET). The percentage the accuracy of the drugs were found to be near to 100% representing the accuracy of the method. The proposed method was also validated and applied for the analysis of the drugs on tablet formulations.